2015
DOI: 10.1007/978-3-662-47989-6_1
|View full text |Cite
|
Sign up to set email alerts
|

Sieving for Shortest Vectors in Lattices Using Angular Locality-Sensitive Hashing

Abstract: Abstract. By replacing the brute-force list search in sieving algorithms with Charikar's angular localitysensitive hashing (LSH) method, we get both theoretical and practical speedups for solving the shortest vector problem (SVP) on lattices. Combining angular LSH with a variant of Nguyen and Vidick's heuristic sieve algorithm, we obtain heuristic time and space complexities for solving SVP in dimension n of 2 0.3366n+o(n) and 2 0.2075n+o(n) respectively, while combining the same ideas with Micciancio and Voul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
107
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(108 citation statements)
references
References 49 publications
1
107
0
Order By: Relevance
“…Now we rewrite f m as p−1 i=0 f i (x i m). Since this sum adds at most 2t terms of each degree, it just remains to be shown that the coefficients of [15,79]) has pushed the heuristic complexity down to 2 0.292...β+o(β) .…”
Section: Proof Of Theorem 21mentioning
confidence: 99%
“…Now we rewrite f m as p−1 i=0 f i (x i m). Since this sum adds at most 2t terms of each degree, it just remains to be shown that the coefficients of [15,79]) has pushed the heuristic complexity down to 2 0.292...β+o(β) .…”
Section: Proof Of Theorem 21mentioning
confidence: 99%
“…end if 17: until v is a shortest vector of the lattice Note that to actually prove (heuristically) that our proposed algorithm achieves a certain heuristic time and space complexity, one should apply the same techniques to the sieve algorithm of Nguyen and Vidick [46] as previously outlined in [32]. Nguyen and Vidick's algorithm comes with heuristic bounds on the time complexity (not based on conjectures on the kissing constant or on the conjectured absence of collisions), and the speedup we obtain applies to that algorithm in the same way.…”
Section: Algorithm 1 the Gausssieve Algorithmmentioning
confidence: 99%
“…Nguyen and Vidick's algorithm comes with heuristic bounds on the time complexity (not based on conjectures on the kissing constant or on the conjectured absence of collisions), and the speedup we obtain applies to that algorithm in the same way. However, similar to [32] we are interested in designing the fastest and most practical sieving algorithm possible for solving SVP rather than the best provable heuristic algorithm, and so in the remainder of this paper we will focus on the GaussSieve. But one should keep in mind that for theoretical arguments these ideas may also be applied to the NV-sieve [46] which actually leads to provable bounds under suitable heuristic assumptions.…”
Section: Algorithm 1 the Gausssieve Algorithmmentioning
confidence: 99%
See 2 more Smart Citations